A Measurement of the W Boson Mass at the Fermilab p p̄ Collider - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; Astur, R; et al. (1998)
We report a measurement of the W boson mass based on an integrated luminosity of 82 pb-1 from pp̄ collisions at √s = 1.8 TeV recorded in 1994-1995 by the D0 detector at the Fermilab Tevatron. We identify W bosons by their decays to e v and extract the mass by fitting the transverse mass spectrum from 28 323 W boson candidates. A sample of 3563 dielectron events, mostly due to Z → ee decays, constrains models of W boson production and the detector. We measure MW = 80.44 ± 0.10(stat) ± 0.07(syst) GeV. By combining this measurement with our result form the 1992-1993 data set, we obtain Mw = 80.43 ± 0.11 GeV.